Tips and Tricks for Safe Retrieval of Tine-based Leadless Pacemakers - Afzal, Muhammad R. (J Innov Card Rhythm Manag, 2021)
As leadless pacing (LP) use is expected to increase, it becomes increasingly essential that operators become familiar with the tools and techniques needed to retrieve an LP successfully. The purpose of this review is to describe a stepwise approach for the successful retrieval of tine-based LP devices, including ways to minimize complications.